2015
DOI: 10.1016/j.ajog.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in early pregnancy and risk of preeclampsia

Abstract: OBJECTIVE-We sought to examine the association between maternal serum 25-hydroxyvitamin D (25[OH]D) concentration in early pregnancy and the subsequent diagnosis of preeclampsia (PE).STUDY DESIGN-This was a nested case-control study from 2 prospective Canadian cohorts conducted in Quebec City, Quebec, and Halifax, Nova Scotia, from 2002 through 2010. Participants were pregnant women (n=169 cases with PE and 1975 controls). Maternal serum was drawn <20 weeks of gestation, and 25(OH)D measurement was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 36 publications
2
57
1
1
Order By: Relevance
“…A relationship between RLS and growing pains has been observed among not only adults but also children, and both have been found to respond to the administration of vitamin D (37). Vitamin D deficiency is not uncommon during pregnancy (38, 39), and this deficiency has been found to be related to impaired dopaminergic neurotransmission through various means (32, 33, 40). Thus, in addition to iron and folate deficiency, vitamin D deficiency might be another contributor to the pathogenesis of RLS during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between RLS and growing pains has been observed among not only adults but also children, and both have been found to respond to the administration of vitamin D (37). Vitamin D deficiency is not uncommon during pregnancy (38, 39), and this deficiency has been found to be related to impaired dopaminergic neurotransmission through various means (32, 33, 40). Thus, in addition to iron and folate deficiency, vitamin D deficiency might be another contributor to the pathogenesis of RLS during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…When this principal component was included as a model predictor, ROC analysis ( model3 AUC: 0.752 (95%CI 0.658, 0.846)) showed that it significantly (p=0.006) outperformed a baseline model including mother’s age, race, site, and gestational age ( model 1 AUC: 0.573 (95%CI 0.463, 0.682)) (Fig 2). Pre-pregnancy BMI, which was significantly associated with risk in this population, and serum vitamin D levels have both previously been shown to predict preeclampsia risk (Achkar et al, 2015, Hyppönen et al, 2013, Bodnar et al, 2014, O’Brien et al, 2003). Therefore models that additionally included pre-pregnancy BMI and baseline serum vitamin D (deficient at <30ng/ml versus sufficient at ≥30ng/ml) ( model 2 AUC: 0.731 (95%CI 0.624, 0.838) were compared.…”
Section: Resultsmentioning
confidence: 65%
“…The summary score based on these features outperformed serum vitamin D. Vitamin D deficiency is thought to play an important role in the pathophysiology of preeclampsia due to its involvement in immunomodulation and placental development (Novakovic et al, 2009), and has previously been shown to be a predictor of risk (Bodnar et al, 2014, Hyppönen et al, 2013, Achkar et al, 2015). The metabolite score also outperformed pre-pregnancy BMI.…”
Section: Discussionmentioning
confidence: 99%
“…There has been an approximate 25% increase in the incidence of preeclampsia in the past 2 decades . Preeclampsia is the leading cause of maternal and perinatal morbidity and mortality . The United States has one of the highest rates of maternal mortality and morbidity among the industrialized countries .…”
Section: Vitamin D Preterm Birth and Preeclampsiamentioning
confidence: 99%